Policy Management to Develop Tourism Work Culture Consciousness and Increasing Visiting People’s Satisfaction - Aldri Frinaldi; Afriva Khaidir; Vivi Yulistia Rahayu (Jurnal Studi Pemerintahan, 2019)
A satisfaction of visitors in Lake Singkarak, District of Solok, West Sumatera is not only influenced by the beauty of the landscape, facilities, and events available but also of the magnitude of satisfaction of the work culture of tourism consciousness by staff who provide a service to the visitors. Awareness is essential to increase visits to the lake. The purpose of this study was to analyze the influence of tourism consciousness work culture by apparatus on visitor’s satisfaction. The research has been done for two consecutive years. The analysis uses quantitative methods in the year 2017 and is continued with qualitative techniques in 2018. The sampling technique is done by purposive sampling. Quantitative data was collected using a Likert scale questionnaire that had been tested for validity and reliability. Before being analyzed using regression, a classic assumption test and analysis of Total Achievement of Respondents (TCR) were examined. Whereas for qualitative data using informants and assisted with interview guides. The findings of the descriptive, in general, show that all elements of the work culture aware of tourism are categorized sufficient, but there are high categories. Then, the results of multiple regression tests influence the variables of work culture on visitor satisfaction to have a significant effect. This is in line with the results in a qualitative manner in general, the visiting community expects an increase in the work culture of tourism awareness among the apparatus and the tourism community around Lake Singkarak, Solok district, to increase community satisfaction visiting the location. Study shows that strengthen in the form of crucial digital governance by the regional government so that the tourism sector can significantly increase tourist visitors from abroad. Boosting performances of the tourism sector as well as accelerate the growth of this sector considerably in the current era cannot only rely on current promotions; it needs information technology touch